2019
DOI: 10.1108/s2516-285320190000002022
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Water Infrastructure Projects’ Financing Challenges in South Africa

Abstract: Purpose-Targets set out by state institutions, with respect to supplying water to deprived communities, seem to be idealistic and not realistic. Study envisioned to assess challenges of financing water infrastructure projects, and determines the role of the state towards infrastructure development by holistically planning and engaging with the private sector. Design/Methodology/Approach-The study adopted a quantitative approach, whereby a questionnaire survey was conducted among different stakeholders involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Several studies (Dithebe et al, 2019a;Fay et al, 2021) have reported on the importance of infrastructure development and how public-private partnerships (PPPs) might be used as a vehicle for delivering SI in both developed and developing economies. However, to date, the majority of the studies have focused more on the critical success factors, (Osei-Kyei and Chan, 2015), drivers ((Janssen et al, 2016;Babatunde andPerera, 2017), andbarriers (Osei-Kyei, andChan, 2017) to the implementation of the PPPs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (Dithebe et al, 2019a;Fay et al, 2021) have reported on the importance of infrastructure development and how public-private partnerships (PPPs) might be used as a vehicle for delivering SI in both developed and developing economies. However, to date, the majority of the studies have focused more on the critical success factors, (Osei-Kyei and Chan, 2015), drivers ((Janssen et al, 2016;Babatunde andPerera, 2017), andbarriers (Osei-Kyei, andChan, 2017) to the implementation of the PPPs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, a number of studies have been undertaken in developing countries aimed at exploring the constraints or barriers facing the lending institutions in the quest for funding infrastructure projects (Dithebe et al, 2019a;Dithebe et al, 2019b;Bolomope et al, 2021;Sinha and Jha, 2021). For instance, within the Indian context, a study by Sihna and Jha (2021) aimed at identifying the problems (constraints) faced by banks, lenders, financial institutions, public authorities, developers, and concessionaires in the course of financing PPP road projects established that whilst the commercial banks in India dominated in providing debt to the PPP infrastructure projects, especially in the road sector, the financing problems faced by the developers resulted in unwarranted time and cost overruns emanating from delay in land acquisition and grant of approvals, hence discouraging private sector participation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other issues including inadequate and variable rainfall, unequal water supply management and the absence of drinking water, bulk water and irrigation facilities, are further factors rendering it impossible for rural villages to distribute water as expected [13]. Ensuring rural water security has become a major challenge for sustainable development due to a growing population, deteriorating water conditions and climate change impacts [14]. This calls for new, imaginative approaches that are ecologically sustainable and cost-effective [15], and also the need to make sure that the municipal water infrastructure is well maintained [8].…”
Section: Service Delivery Of Watermentioning
confidence: 99%
“…[17] despite the importance of water to livelihoods, over 783 million of the world's population has no access to clean water. Challenges encountered concerning the delivery of water to the public include but not limited to miscommunication between different water agencies, limited resources, leakages in official spending and lack of monitoring progress of different water projects, [14]. A government body's delivery of a service can be considered as a process of producing value for a number of different stakeholders, [12] furthermore, the stakeholders will participate at different points in the value-network and therefore will interact with different government systems [12].…”
Section: Service Delivery Of Watermentioning
confidence: 99%